Impact of Natural Environment to Sustainable Development of Tourism - Sultonovich, Sayfutdinov Shukhratjon; Yunusbayevna, Gapparova Umida (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Sustainable tourism is affects the environment of the host country, where tourists conduct their activities, tourism boosts the economy. In order to assess the contribution of tourism to sustainability, the study paper looks into how tourism affects the environment. For an in-depth investigation, the researcher has thought about gathering qualitative data from multiple sources. To extract more qualitative data to support the study's purpose, an inductive approach has been used. The research showed that tourism has an impact on the environment, as evidenced by the economic, health, and social factors that have both good and bad effects.